Nanoparticle–cell interactions induced apoptosis: a case study with nanoconjugated epidermal growth factor. Issue 14 (28th March 2018) - Khanehzar, Ali; Fraire, Juan C.; Xi, Min; Feizpour, Amin; Xu, Fangda; Wu, Linxi; Coronado, Eduardo A.; Reinhard, Björn M.
Abstract : In addition to the intrinsic toxicity associated with the chemical composition of nanoparticles (NP) and their ligands, inert biofunctionalized NP can perturb cellular processes and induce apoptosis. Abstract : In addition to the intrinsic toxicity associated with the chemical composition of nanoparticles (NP) and their ligands, biofunctionalized NP can perturb specific cellular processes through NP–cell interactions and induce programmed cell death (apoptosis). In the case of the epidermal growth factor (EGF), nanoconjugation has been shown to enhance the apoptotic efficacy of the ligand, but the critical aspects of the underlying mechanism and its dependence on the NP morphology remain unclear. In this manuscript we characterize the apoptotic efficacy of nanoconjugated EGF as a function of NP size (with sphere diameters in the range 20–80 nm), aspect ratio (A.R., in the range of 4.5 to 8.6), and EGF surface loading in EGFR overexpressing MDA-MB-468 cells. We demonstrate a significant size and morphology dependence in this relatively narrow parameter space with spherical NP with a diameter of approx. 80 nm being much more efficient in inducing apoptosis than smaller spherical NP or rod-shaped NP with comparable EGF loading. The nanoconjugated EGF is found to trigger an EGFR-dependent increase in cytoplasmic reactive oxygen species (ROS) levels but no indications of increased mitochondrial ROS levels or mitochondrial membrane damage are detected at early time points of the apoptosis induction. The increase in cytoplasmic ROS is accompanied by a perturbation of the intracellular glutathione homeostasis, which represents an important check-point for NP-EGF mediated apoptosis. Abrogation of the oxidative stress through the inhibition of EGFR signaling by the EGFR inhibitor AG1478 or addition of antioxidants N -acetyl cysteine (NAC) or tempol, but not trolox, successfully suppressed the apoptotic effect of nanoconjugated EGF. A model to account for the observed morphology dependence of EGF nanoconjugation enhanced apoptosis and the underlying NP–cell interactions is discussed.